2020
DOI: 10.3389/fphar.2020.606097
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SARS-CoV-2 by Highly Potent Broad-Spectrum Anti-Coronaviral Tylophorine-Based Derivatives

Abstract: Tylophorine-based compounds and natural cardiotonic steroids (cardenolides and bufadienolides) are two classes of transmissible gastroenteritis coronavirus inhibitors, targeting viral RNA and host cell factors, respectively. We tested both types of compounds against two types of coronaviruses, to compare and contrast their antiviral properties, and with view to their further therapeutic development. Examples of both types of compounds potently inhibited the replication of both feline infectious peritonitis vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Cells were pretreated with serial dilutions of remdesivir and cyclosporine at the indicated concentrations for 0.5 h prior to HCoV-OC43 infection at an MOI of 0.05. At 30 h.p.i., the resulting adherent cells were then fixed with 4% formaldehyde, permeabilized with 100% methanol, and subsequently subjected to IFA analyses with an antibody against HCoV-OC43 N protein (Mab9013) and FITC-conjugated anti-mouse immunoglobulin (#55499) (green), and the EC 50 values determined as described ( Yang et al, 2020 ). CC 50 values were determined by staining nuclei blue with Hoechst dye and then determining relative cell viability using the number of nuclei in the vehicle control as 100%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were pretreated with serial dilutions of remdesivir and cyclosporine at the indicated concentrations for 0.5 h prior to HCoV-OC43 infection at an MOI of 0.05. At 30 h.p.i., the resulting adherent cells were then fixed with 4% formaldehyde, permeabilized with 100% methanol, and subsequently subjected to IFA analyses with an antibody against HCoV-OC43 N protein (Mab9013) and FITC-conjugated anti-mouse immunoglobulin (#55499) (green), and the EC 50 values determined as described ( Yang et al, 2020 ). CC 50 values were determined by staining nuclei blue with Hoechst dye and then determining relative cell viability using the number of nuclei in the vehicle control as 100%.…”
Section: Methodsmentioning
confidence: 99%
“…For IFA used in the SARS-CoV-2 study, Vero E6 cells (BCRC number: 60476; derived from ATCC CRL-1586) were passaged within 6 months of receipt and the 4th–15th passages used. Cells were pretreated with each compound at the indicated concentration for 1 h at 37°C and then adsorbed with SARS-CoV-2 (TCDC#4) (sequence available on the GISAID website) at 100 PFU (MOI = 0.01) for 1 h at 37°C as described ( Yang et al, 2020 ). The virus-containing supernatants were removed and then fresh medium containing each compound at the indicated concentrations added to the cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with topotecan, an analog of the plant-derived alkaloid camptothecin, reduced morbidity and mortality rates in mice infected with SARS-CoV-2, with indications of reduced inflammatory responses (Ho et al, 2021). Derivatives of tylophorine, a naturally occurring alkaloids, have also demonstrated the ability to inhibit SARS-CoV-2 infection in vitro (Yang et al, 2020).…”
Section: Alkaloidsmentioning
confidence: 99%
“…Some previous studies have shown that Tylophora alkaloids can inhibit viral protease and suppresses viral RNA replication by blocking the JAK2 mediated NF-κB activation (49). While tylophorine derivatives have inhibitory effects on mouse hepatitis virus (MHV), transmissible gastroenteritis virus (TGEV), and SARS-CoV (50)(51)(52). A recent report revealed that Tylophora alkaloids could inhibit the CoV-infected cells of swine (53).…”
Section: Selection Of Plants and The Rationalementioning
confidence: 99%